History of Illicit Stimulant Use Is Not Associated with Long-Lasting Changes in Learning of Fine Motor Skills in Humans. (27th December 2015) - Todd, Gabrielle; Pearson-Dennett, Verity; Flavel, Stanley C.; Haberfield, Miranda; Edwards, Hannah; White, Jason M.
Abstract : Little is known about the long-lasting effect of use of illicit stimulant drugs on learning of new motor skills. We hypothesised that abstinent individuals with a history of primarily methamphetamine and ecstasy use would exhibit normal learning of a visuomotor tracking task compared to controls. The study involved three groups: abstinent stimulant users (n = 21 ; 27 ± 6 yrs) and two gender-matched control groups comprising nondrug users (n = 16 ; 22 ± 4 yrs) and cannabis users (n = 16 ; 23 ± 5 yrs). Motor learning was assessed with a three-minute visuomotor tracking task. Subjects were instructed to follow a moving target on a computer screen with movement of the index finger. Metacarpophalangeal joint angle and first dorsal interosseous electromyographic activity were recorded. Pattern matching was assessed by cross-correlation of the joint angle and target traces. Distance from the target (tracking error) was also calculated. Motor learning was evident in the visuomotor task. Pattern matching improved over time (cross-correlation coefficient) and tracking error decreased. However, task performance did not differ between the groups. The results suggest that learning of a new fine visuomotor skill is unchanged in individuals with a history of illicit stimulant use.